PEMBERONTAKAN MARTABAT MANUSIA SEBAGAI DASAR HAM TERHADAP PENINDASAN KAPITALISME DALAM DIMENSI FILSAFAT KARL MARX - Fransiskus Saverius Nurdin (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2019)
The extreme demarcation line between humans and animals is dignity. Dignity is only inherently inherent in humans since humans are in the mother's womb, whereas animals have no dignity. That dignity is what drives other human beings morally socially obliged to respect other human beings without conditions. Recognition and respect for human beings is actually recognized as an inherent right that cannot be separated. This understanding becomes the entry point of this writing to position humans as dignified creatures. This paper aims to describe the Marxian philosophy of human freedom (dignity) deconstructed by capitalism. History records that capitalism is a disaster of human civilization. Capitalism has re-identified humans. This paper is a library research writing using the philosophical approach. The nature of this paper is descriptive-analytical. The issue of dignity as the basis of human rights in this paper is not described in the framework of legal norms (Law). At the end of this paper the author concludes the alienation that causes humans to fight for their dignity by the suppression of capitalism.